O problema da fonte da inteligibilidade na ontologia hermenêutica de Martin Heidegger - Michels, Bruno de Prá (2014)
The central theme of the fundamental ontology of Martin Heidegger is the question of the meaning of being. In a first approximation, one can say that the Heidegger s project in Being and Time is to elucidate the ways of being that regulate how the entities receive their determinations. In order to address adequately the issue so, Heidegger in Being and Time develops a phenomenology of human existence as being-in-world. According to description of everyday life the entities acquire identity and meaning within the world, understood as the space of meaning held previously for understanding. The Anglo-American reception of fundamental ontology raised the problem of the sources of intelligibility of Dasein s world. This is the problem of identifying the transcendental structures responsible for the formation of the space of meaning. Charles Guignon argues that language is the source of the intelligibility in Heidegger s hermeneutic ontology. However, Dreyfus argues that it is the one (das Man) fulfills that role. Rejecting both readings, Weberman and Keller argue that Heidegger finds in the temporality of human existence the source of intelligibility. From the perspective of these authors, Guignon Dreyfus fail because they exhibit conditions necessary but not sufficient for intelligibility. The goal of this dissertation is to reconstruct this debate about the sources of intelligibility in Heidegger s fundamental ontology.